2021
DOI: 10.3390/jcm10050985
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness and Safety of Once-Weekly GLP-1 Receptor Agonist Dulaglutide as Add-On to Metformin or Metformin Plus Insulin Secretagogues in Obesity and Type 2 Diabetes

Abstract: Aims and methods: The aim of this monocentric retrospective observational study was to evaluate the 18-month safety and effectiveness of GLP-1 receptor agonist (GLP-1 RA) dulaglutide (DU) 1.5 mg/once weekly as an add-on to metformin (MET) or MET plus conventional insulin secretagogues in a study cohort with excess body weight and type 2 diabetes (T2D). Comparative efficacy versus liraglutide (LIRA) 1.2–1.8 mg/once daily in a study sample naïve to GLP-1 RAs, frequency matching for age, gender, T2D duration, deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Alongside nutrition therapies, pharmacological interventions for diabetes have been suggested to influence cancer risk in affected patients. However, if the use of insulin analogues and conventional insulin secretagogues, which lead to increased levels of circulating insulin [ 290 ], has been associated with increased risk of cancer [ 121 , 122 , 291 , 292 ], metformin and thiazolidinediones (TZDs) may have the potential to prevent tumor development.…”
Section: Antidiabetic Medications As Potential Anticancer Agentsmentioning
confidence: 99%
“…Alongside nutrition therapies, pharmacological interventions for diabetes have been suggested to influence cancer risk in affected patients. However, if the use of insulin analogues and conventional insulin secretagogues, which lead to increased levels of circulating insulin [ 290 ], has been associated with increased risk of cancer [ 121 , 122 , 291 , 292 ], metformin and thiazolidinediones (TZDs) may have the potential to prevent tumor development.…”
Section: Antidiabetic Medications As Potential Anticancer Agentsmentioning
confidence: 99%
“…5,6 Both glucagon-like peptide-1 (GLP-1) receptor agonists and sodium-glucose cotransporter-2 (SGLT-2) inhibitors are associated with better blood glucose control, greater body weight reduction, lower mortality, and lower incidence of cardiovascular events in the general population with diabetes. [7][8][9] According to the American Diabetes Association guideline, 10 GLP-1 receptor agonist treatment is recommended for patients with diabetes and CKD who have an estimated glomerular filtration rate less than 60 mL/min/1.73 m 2 and are at risk for cardiovascular disease. According to the Kidney Disease: Improving Global Outcomes 2020 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease, 11,12 GLP-1 receptor agonist treatment is suggested for individuals who are unable to use metformin or SGLT-2 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Among 408 patients with T2DM, 66 patients stopped SGLT2i because of chronic or recurring genital infections [ 24 ]. They also reported that 13 out of 126 participants with T2DM discontinued dulaglutide due to moderate-severe gastrointestinal AEs [ 25 ]. In the present survey, we showed the superiority of the concomitant use of GLP1Ra during the SGLT2i treatment compared with the concomitant use of DPP4i, especially on the change in eGFR; however, the use of GLP1Ra and SGLT2i may increase the frequency of AEs or the deterioration of eGFR.…”
Section: Discussionmentioning
confidence: 99%